Microscopic Investigation of Rate Dependence on Three-Point Notched-Tip Bending Sandstone - Wenshuai Li; Faiz U. A. Shaikh; Lianguo Wang; Yinlong Lu; Kai Wang; Zhaolin Li (Shock and Vibration)
The cracking process in rock or concrete is usually characterized by the formation of microcracks that eventually form a propagating macrocrack. A series of three-point bending experiments were performed on sandstone containing Mode I crack under different loading rates. The microscopic monitoring system was established to capture the cracking process at notch tip. The loading rate dependence of microcracking behaviour was analysed based on load-time curves, acoustic emission (AE), microscopic images, and micrograph-based digital image correlation (DIC) technology. Results showed that the specimens underwent a short period of compression and elastic deformation stage under high loading rate, and the peak loads increased with the increase in loading rate. The AE results revealed that the fracturing process can be divided into elastic stage, damage stage, and postpeak stage, and more extensive damage occurred before the peak under low loading rate. It can be observed from microscopic images that the crack was initiated during the elastic stage, which was earlier than that determined from the AE monitoring. In addition, the microcracks were initiated at multiple locations and were mainly located at the interfaces between dense grains under low loading rate, while microcracks were observed inside the grains under high loading rate. Furthermore, the DIC results showed that the crack opening displacement (COD) of 0.6 mm/min at the peak was almost twice than that of 3.0 mm/min. The COD under the same loading rate at the peak can be considered as the material property of sandstone.